The impact of medical and social rehabilitation on the adaptation of the elderly to modern social and legal processes - Anishchenko, M. A.; Myrna, A. I.; Myrnyi, D. P.; Bukanov, H. M.; Taran, V. O.; Аніщенко, Михайло Анатолійович (My University, 2021)
The article is devoted to the peculiarities of the process of medical and social rehabilitation of the elderly, which an increasing number of people of this age category requires. The paper examines the main causes and problems in the lives of the elderly, leading to their loss of physical and social activity, and subsequently to social isolation and misadaption of representatives of the specified age category. The article explores the relationship between the medical and social rehabilitation of the elderly and their participation in social and legal processes. The results of the most highly-publicized studies of scientists from different countries of the world concerning the problems of medical and social rehabilitation of the elderly and the importance of this process for society have been analyzed. Recommendations on the introduction of effective technologies of medical and social rehabilitation of the elderly, their impact on social and legal processes have been proposed.
Keywords: medical rehabilitation; social rehabilitation; physical rehabilitation; the elderly; medical and social support